Preparation method of intermediate carbon microspheres

Through low-temperature thermal polycondensation process and hydrotreatment combined with catalytic polycondensation reaction and carbonization treatment, the problems of uneven particle size distribution and poor spherical degree of intermediate carbon microspheres are solved, and high-quality and low-cost preparation of intermediate carbon microspheres are achieved.

CN119612480AActive Publication Date: 2025-03-14PETROCHINA CO LTD

Patent Information

Application Number
CN202311189108.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-14
Estimated Expiration
2043-09-14

AI Technical Summary

Technical Problem

The prior art has problems such as uneven particle size distribution, poor spherical shape and high industrial production costs when preparing intermediate carbon microspheres.

Method used

The precursor asphalt is treated by a low-temperature thermal polycondensation process combined with hydrotreatment, and the precursor asphalt is treated by isomerization functional catalyst and molecular sieve catalyst. Then, the catalytic polycondensation reaction is carried out under the action of heteropolyaluminum salt and heteropolya iron salt catalyst. Finally, the mesophase carbon microspheres with uniform particle size distribution and good spherical shape are obtained through organic solvent or oil fraction extraction and carbonization treatment.

Benefits of technology

The uniformity of the particle size distribution and spherical degree of carbon microspheres have been achieved, the cost of industrial production is reduced, and it is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612480A_ABST
    Figure CN119612480A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of intermediate carbon microspheres, which comprises the following steps of: preparing precursor asphalt by taking naphthenic base aromatic hydrocarbon-rich heavy oil as a raw material and adopting a low-temperature thermal polycondensation process; the preparation method comprises the following steps: carrying out fluidized bed hydrotreatment on precursor asphalt under proper reaction conditions by matching with a proper isomerization functional catalyst and a molecular sieve catalyst to obtain refined aromatic hydrocarbon-rich distillate oil with a boiling range of more than 400 DEG C, and taking the refined aromatic hydrocarbon-rich distillate oil as a raw material; the preparation method comprises the following steps: carrying out a catalytic polycondensation reaction under the dual catalytic action of a heteropolyacid aluminum salt catalyst and a heteropolyacid ferric salt catalyst to obtain intermediate pitch, extracting the intermediate pitch through an extraction solvent, removing isotropic pitch components to obtain green carbon microspheres, and finally carrying out carbonization treatment on the green carbon microspheres to obtain the mesocarbon microbeads. The invention provides a brand new aromatic hydrocarbon-rich raw material refining treatment process through technical coupling, has the advantages of wide raw material application range and high production efficiency, and opens up a new path for low cost and high quality of mesocarbon microbeads.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the research field of carbonaceous mesophase materials, and in particular relates to a method for preparing mesocarbon microspheres. Background Art

[0002] In recent years, the world's crude oil resources have shown a trend of becoming heavier, especially those with a density greater than 0.93cm 3 / g of heavy oil processing ratio is gradually increasing, which makes the output of heavy residue oil in the process of petroleum refining gradually increase. These heavy residue oils have relatively complex structure and composition, large molecular weight distribution range, and contain a certain amount of S, N, O and heavy metal elements. It is difficult to achieve pollution-free and high-value utilization by traditional refining technology. However, heavy residue oil, such as FCC slurry, ethylene tar, etc., is rich in short side chain polycyclic aromatic hydrocarbons (mainly 2 to 5 rings), which is considered to be a potential high-quality raw material for the preparation of functional carbon materials such as mesophase carbon microspheres, needle coke, mesophase pitch-based carbon fibers, foam carbon, etc.

[0003] Mesocarbon microbeads (MCMB) are spherical micron-sized soft carbon materials formed by the parallel stacking of planar condensed aromatic macromolecules. Their particle sizes are mainly distributed between 1 and 40 μm. The special structural characteristics of carbon microbeads enable them to exhibit excellent electrochemical properties. The common structural type of MCMB is the globe-shaped structure (also known as the Brook-Taylor type, or the latitude type). The internal carbon layers of this type of carbon microbeads are stacked parallel to each other, and their layered carbon layer structure produces a large intercalation lithium storage capacity. In addition, MCMB has a natural micron-sized spherical structure, which also enables MCMB to achieve dense stacking and provide high volume energy density. Therefore, MCMB has irreplaceable advantages over other lithium-ion battery negative electrode materials.

[0004] Chinese patent CN109179371A provides a method for preparing mesophase carbon microspheres using asphalt thermal cracking oil. The method obtains aromatics-rich feedstock oil by hot filtration coupled with solvent extraction, and then uses a thermal polycondensation process to prepare a product asphalt containing mesophase beads. The mesophase carbon microspheres are obtained after solvent extraction, filtration, and high-temperature carbonization. The method has a low yield for preparing carbon microspheres, a wide range of microsphere particle size distribution, and melting and agglomeration between carbon microspheres. Patent CN103613089A discloses a method for preparing mesophase carbon microspheres using coal liquefaction residues. The method first uses a solvent extraction process to remove solid impurities in the coal liquefaction residues to obtain asphaltene-like substances, and then adds a polycondensation solvent and a nucleating agent under certain reaction conditions. The product asphalt containing mesophase spheres is obtained by heat treatment under the condition of low temperature, and the mesophase carbon microspheres are obtained after solvent washing, filtering and drying. This method realizes the efficient utilization of coal liquefaction residue oil, but the obtained mesophase carbon microspheres have a large particle size, poor sphericity and low yield; Patent CN1308113A discloses a co-condensation preparation method for mesophase carbon microspheres, which uses medium-temperature coal tar and petroleum heavy oil containing quinoline insolubles as raw materials, and prepares the product asphalt containing mesophase spheres by co-condensation reaction under high temperature conditions, and uses a mixed solution of coal tar and light distillate oil of petroleum as an extractant, and obtains the mesophase carbon microspheres after hot filtration and drying, but this method has the disadvantages of large carbon microsphere particle size, low yield and difficult recovery of the extractant.

[0005] In summary, some existing processes are prone to problems such as uneven particle size distribution of carbon microspheres, poor sphericity, and low yield when preparing intermediate carbon microspheres. In addition, in the extraction process, only organic solvents are generally used for extraction, resulting in high costs and difficulty in industrial production. Therefore, it is necessary to develop a new method for preparing high-quality intermediate carbon microspheres to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing intermediate carbon microspheres, which solves the problems of uneven particle size distribution, poor sphericity and high industrial production cost of carbon microspheres prepared in the prior art.

[0007] The technical solution adopted by the present invention is a method for preparing intermediate carbon microspheres, comprising the following steps:

[0008] S1: Using naphthenic aromatic-rich heavy oil as raw material, a low-temperature thermal polycondensation process is used to prepare precursor asphalt;

[0009] S2: The precursor asphalt is treated with ebullated bed hydrogenation using an isomerization catalyst and a molecular sieve catalyst, and then a vacuum distillation process is performed to obtain a refined aromatic-rich fraction oil;

[0010] S3: Using the refined aromatic-rich fraction oil as raw material, a catalytic polycondensation reaction is carried out under the dual catalytic action of a heteropolyacid aluminum salt catalyst and a heteropolyacid iron salt catalyst to obtain an intermediate pitch containing mesophase beads, and the intermediate pitch is extracted by an organic solvent or an oil fraction to obtain carbon microspheres;

[0011] S4: Carbon microspheres are carbonized or pre-oxidized and carbonized to obtain intermediate carbon microspheres.

[0012] The present invention is also characterized in that: the reaction temperature of the low-temperature thermal polycondensation process is 300°C to 400°C, the reaction time is 10min to 120min, and the reaction pressure is 0.1MPa to 3MPa;

[0013] The temperature of the ebullient bed hydrogenation process is 380℃~460℃, the hydrogen partial pressure is 0.5MPa~6MPa, and the space velocity is 0.1h -1 ~10h -1 ;

[0014] The isomerization functional catalyst is selected from one or more of AlCl3, SbCl, acidified Al2O3 or molybdenum oxide, the molecular sieve catalyst is selected from silicon aluminum molecular sieve or phosphorus aluminum molecular sieve, and the molecular sieve catalyst is loaded with one or more of Pt, Pd or Ni;

[0015] The negative pressure of the vacuum distillation process is 1-5 mmHg, the theoretical number of towers is 5-20, the reflux ratio is 1:5-5:1, and the liquid phase distillation temperature is 330-350°C;

[0016] The heteropolyacid aluminum salt catalyst is selected from one or more of phosphate aluminum acid, silicic acid aluminum acid or potassium phosphate aluminum salt, and the addition amount of the heteropolyacid aluminum salt catalyst is 0.5-5wt%;

[0017] The heteropolyacid iron salt catalyst is selected from one or more of ferrophosphite, ferrophosphite divanadate or ferrophosphite trivanadate, and the addition amount of the heteropolyacid iron salt is 0.5-5wt%;

[0018] The catalytic polycondensation reaction temperature is 350°C to 450°C, the reaction pressure is 0.1 to 3 MPa, and the reaction time is 2 to 10 hours;

[0019] The organic solvent is selected from one or more of tetrahydrofuran, N-dimethylamide or dimethyl sulfoxide, and the solvent-oil ratio during the extraction process is 4:1 to 10:1;

[0020] The oil fraction is selected from gasoline fraction with a boiling range of 130-200°C, diesel fraction with a boiling range of 200-350°C, or a mixed fraction of the two with a mass ratio of 5:1-1:5. The agent-oil ratio in the extraction process is 1:1-10:1.

[0021] The pre-oxidation treatment temperature is 220°C to 280°C, the oxygen flow rate is 100 to 300 ml / min, and the pre-oxidation treatment time is 2h to 6h; the carbonization temperature is 800°C to 1600°C, the nitrogen flow rate is 100 to 300 ml / min, and the carbonization treatment time is 0.5h to 3h.

[0022] The beneficial effects of the present invention are:

[0023] 1. The present invention utilizes a low-temperature thermal polycondensation process coupled with selective hydrogenation treatment to achieve molecular structure composition control of the crude oil, improve the molecular conversion efficiency of aromatic hydrocarbons in the later catalytic polycondensation process, and achieve simultaneous improvement of the microstructure characteristics and macroscopic performance of the carbon microspheres. The obtained carbon microspheres have uniform particle size distribution and good sphericity.

[0024] 2. The present invention provides a new refining process for aromatic-rich raw materials through technical coupling. The disclosed method for treating aromatic-rich raw materials can meet the treatment requirements of aromatic-rich raw oils with different properties. It has the advantages of low industrial production cost, large operating space, high universality, uniform particle size distribution of finished carbon microspheres, and good sphericity, which opens up a new path for the low-cost and high-quality industrial production of mesophase carbon microspheres. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the SEM image of mesocarbon microspheres in Example 1;

[0026] Figure 2 This is the average particle size distribution diagram of mesophase carbon microspheres in Example 1;

[0027] Figure 3 is the SEM image of mesocarbon microspheres in Example 2;

[0028] Figure 4 is a histogram of average particle size of mesophase carbon microspheres in Example 2;

[0029] Figure 5 is the SEM image of mesocarbon microspheres of Example 3;

[0030] Figure 6 This is a histogram of the average particle size of the mesophase carbon microspheres in Example 3. DETAILED DESCRIPTION

[0031] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] A method for preparing mesocarbon microspheres comprises the following steps:

[0033] S1: Using cycloalkyl aromatic-rich heavy oil as raw material, a low-temperature thermal polycondensation process is adopted to prepare a precursor asphalt; wherein, the cycloalkyl aromatic-rich heavy oil can use catalytic cracking (FCC) slurry, ethylene tar, etc.; the reaction temperature of the low-temperature thermal polycondensation process is 300°C to 400°C, the reaction time is 10min to 120min, and the reaction pressure is 0.1MPa to 3MPa.

[0034] S2: The precursor asphalt is subjected to ebullient bed hydrogenation treatment with an isomerization functional catalyst and a molecular sieve catalyst, and then a vacuum distillation process is used to obtain a refined aromatic-rich distillate oil, specifically a refined aromatic-rich distillate oil with a boiling range greater than 400°C. The hydrogenation temperature is 380°C to 460°C, the hydrogen partial pressure is 0.5MPa to 6MPa, and the space velocity is 0.1h -1 ~10h -1 The isomerization functional catalyst is selected from one or more of AlCl3, SbCl, acidified Al2O3, and molybdenum oxide, and the molecular sieve catalyst is selected from silicon aluminum molecular sieve or phosphorus aluminum molecular sieve loaded with Pt, Pd or Ni; wherein, the vacuum distillation process negative pressure is 1 to 5 mmHg, the theoretical plate number is 5 to 20, the reflux ratio is 1:5 to 5:1, and the liquid phase distillation temperature is 330 to 350°C.

[0035] S3: Using refined aromatic-rich fraction oil as raw material, a catalytic polycondensation reaction is carried out under the dual catalytic action of heteropolyacid aluminum salt catalyst and heteropolyacid iron salt catalyst to obtain an intermediate asphalt containing mesophase beads, and the intermediate asphalt is extracted by an organic solvent or oil fraction to remove the isotropic asphalt component to obtain carbon microspheres;

[0036] The aluminum salt of heteropolyacid is selected from one or more of phosphate aluminum acid, silicic acid aluminum acid or potassium phosphate aluminum acid salt, the addition amount of the aluminum salt of heteropolyacid is 0.5-1.5wt%, the iron salt of heteropolyacid is selected from one or more of phosphoferric acid, phosphoferric divanadic acid and phosphoferric trivanadic acid, the addition amount of the iron salt of heteropolyacid is 0.5-1.5wt%, the catalytic polycondensation reaction temperature is 350°C-450°C, the reaction pressure is 0.1-3MPa, and the reaction time is 2h-10h;

[0037] Furthermore, the organic solvent is selected from one or more of tetrahydrofuran, N-dimethylamide or dimethyl sulfoxide, and the agent-oil ratio during the extraction process is 4:1 to 10:1; the oil fraction is selected from a gasoline fraction with a boiling range of 130 to 200°C, including a straight-run gasoline fraction, a catalytic cracking gasoline fraction or a coking gasoline fraction, etc., and a diesel fraction with a boiling range of 200 to 350°C can also be selected, including a straight-run diesel fraction, a catalytic cracking diesel fraction, a coking diesel oil fraction, etc., or a mixed fraction of the two in a mass ratio of 5:1 to 1:5, and the agent-oil ratio during the extraction process is 1:1 to 10:1.

[0038] S4: carbonizing or pre-oxidizing and carbonizing the raw carbon microspheres to obtain mesophase carbon microspheres with uniform particle size distribution and good sphericity;

[0039] In the present invention, the pre-oxidation treatment temperature is 220°C to 280°C, the oxygen flow rate is 100 to 300 ml / min, the pre-oxidation treatment time is 2h to 6h, the carbonization temperature is 800°C to 1600°C, the nitrogen flow rate is 100 to 300 ml / min, and the carbonization treatment time is 0.5h to 3h. It is worth noting that: in actual production, carbonization treatment can be carried out directly, or pre-oxidation treatment can be carried out first, and then carbonization treatment can be carried out. Pre-oxidation will reduce the burden of subsequent carbonization and will make the finished product yield higher or the quality better.

[0040] The present invention aims at the structural composition characteristics of cycloalkane heavy oil, realizes the regulation of the structural composition of aromatic molecules by coupling a low-temperature thermal polycondensation process with a hydrogenation treatment, and then enriches polycyclic aromatic molecules with similar molecular weights and similar structural compositions by means of a vacuum distillation process to obtain refined aromatic-rich fraction oil. Among them, the low-temperature polycondensation treatment can improve the polycondensation degree of aromatic molecules to a certain extent, so that the number of aromatic rings in the molecule reaches 3-5, and the moderate hydrogenation treatment can significantly increase the number of alkyl side chains around the aromatic molecules, so that they have higher reaction activity, which is conducive to the rapid polycondensation of aromatic molecules in the later high-temperature carbonization process. Heteropolyacid iron salt and heteropolyacid aluminum salt are selected as catalysts, and product asphalt containing mesophase beads is prepared under certain reaction conditions. In the reaction system, the addition of heteropolyacid aluminum salt can effectively stimulate the activation of crude oil molecules, reduce the reaction temperature, and avoid excessive polycondensation of mesophase asphalt molecules. Heteropolyacid iron salt is both an initiator and a nucleating agent, inducing the formation of mesophase beads and improving the conversion rate. At the same time, the pyrolysis products of heteropolyacid aluminum salt and heteropolyacid iron salt will be adsorbed on the surface of the mesophase beads to avoid mutual fusion, improve the sphericity of carbon microspheres, and reduce the particle size distribution range of carbon microspheres. Solvent extraction process is used to separate the mesophase beads and isotropic asphalt components, which can quickly separate and enrich the mesophase beads. At the same time, the extracted isotropic asphalt product can also be used as impregnation asphalt, further expanding the application field of crude oil.

[0041] Embodiment 1:

[0042] 280g of FCC oil slurry was added into a high temperature and high pressure reactor and reacted at 300℃ and 0.1MPa for 120min. Then, the product asphalt was transported to the fluidized bed by pipeline pump. AlCl3 and Pt-loaded aluminum phosphorus molecular sieve were used as catalysts. The reaction temperature was set to 420℃, the hydrogen partial pressure was 4MPa, and the space velocity was 5h. -1The product after hydrogenation was transported to a vacuum distillation device for treatment at a negative pressure of 1 mmHg, 5 theoretical plates, a reflux ratio of 1:5, and a liquid distillation temperature of 350°C to obtain a refined aromatic-rich fraction oil with a boiling range greater than 400°C; 200 g of the refined fraction oil was weighed and placed in a high-temperature and high-pressure reactor, 1 g of phosphoaluminic acid and 1 g of phosphoferric acid were added, and the mixture was reacted at 350°C and 0.1 MPa for 10 h to obtain a two-phase coexistence asphalt containing mesophase globules, with The 200°C straight-run gasoline fraction was used as the extraction solvent, and the agent-oil ratio was 1:1 during the extraction process. Carbon microspheres were obtained by multiple elutions, and then the pre-oxidation temperature was set to 220°C, the oxygen flow rate was 100 ml / min, and the pre-oxidation time was 6 h for pre-oxidation treatment. Then, carbonization treatment was carried out at 800°C for 3 h in a nitrogen atmosphere, wherein the nitrogen flow rate was 100 ml / min, to obtain carbon microspheres with an average particle size of 19.8 μm, uniform particle size distribution, and good sphericity.

[0043] Example 1 The SEM images and average particle size measurement statistical results of mesophase carbon microspheres are shown as follows: Figure 1 , Figure 2 shown.

[0044] Embodiment 2:

[0045] 280g of ethylene tar was added into a high-temperature and high-pressure reactor and reacted at 400℃ and 2MPa for 10min. Then, the product asphalt was transported to the ebullient bed by a pipeline pump. The SbCl and Pd-loaded phosphoaluminum molecular sieve was used as the catalyst. The reaction temperature was set to 380℃, the hydrogen partial pressure was 0.5MPa, and the space velocity was 0.1h -1 The product after hydrogenation was transported to a vacuum distillation device for treatment at a negative pressure of 5 mmHg, 15 theoretical plates, a reflux ratio of 1:1, and a liquid distillation temperature of 340°C to obtain a refined aromatic-rich fraction oil with a boiling range greater than 400°C; 200 g of the refined fraction oil was weighed and placed in a high-temperature and high-pressure reactor, 3 g of phosphoaluminic acid and 3 g of phosphoferric acid were added, and the mixture was reacted at 450°C and 3 MPa for 2 h to obtain a two-phase coexistence asphalt containing mesophase globules, and 25 The straight-run diesel fraction at 0°C was used as the extractant, and the agent-oil ratio was 10:1 during the extraction process. Carbon microspheres were obtained by multiple elutions, and then the pre-oxidation temperature was set to 250°C, the oxygen flow rate was 200ml / min, and the pre-oxidation time was 4h for pre-oxidation treatment. Then, carbonization treatment was carried out at 1600°C in a nitrogen atmosphere for 0.5h, with a nitrogen flow rate of 200ml / min, to obtain carbon microspheres with an average particle size of 15.5μm, uniform particle size distribution and good sphericity.

[0046] Example 2 The SEM images and average particle size measurement statistical results of the mesophase carbon microspheres are shown as follows: Figure 3 , Figure 4 shown.

[0047] Embodiment 3:

[0048] 280g of catalytic cracking oil slurry was added into a high-temperature and high-pressure reactor and reacted at 350℃ and 3MPa for 60min. Then, the product asphalt was transported to the fluidized bed by a pipeline pump. The acidified Al2O3 and Ni-loaded phosphoaluminum molecular sieve were used as catalysts. The reaction temperature was set to 460℃, the hydrogen partial pressure was 6MPa, and the space velocity was 10h -1 The hydrogenation treatment was carried out under the conditions of 3 mmHg, and the hydrogenated product was transported to the vacuum distillation device for treatment, with a negative pressure of 3 mmHg, 20 theoretical plates, a reflux ratio of 5:1, and a liquid distillation temperature of 330 ° C. 200 g of refined distillate oil was weighed and placed in a high-temperature and high-pressure reactor, 2 g of phosphoaluminic acid and 2.5 g of phosphoferric acid were added, and the reaction was carried out at 400 ° C and 2 MPa for 6 h to obtain a two-phase coexistence asphalt containing mesophase beads, and a mixed fraction of 130 ° C catalytic cracking gasoline fraction and 250 ° C coking diesel oil fraction with a mass ratio of 5:1 was used as the extractant. The agent-oil ratio during the extraction process was 5:1. Carbon microspheres were obtained by multiple elutions, and then carbonized for 2 h in a nitrogen atmosphere at 1200 ° C, wherein the nitrogen flow rate was 300 ml / min, and carbon microspheres with an average particle size of 16.6 μm were obtained, with uniform particle size distribution and good sphericity.

[0049] Example 3 The SEM images and average particle size measurement statistical results of mesophase carbon microspheres are shown as follows: Figure 5 , Figure 6 shown.

[0050] Embodiment 4:

[0051] 280g of catalytic cracking oil slurry was added into a high-temperature and high-pressure reactor and reacted at 350℃ and 3MPa for 60min. Then, the product asphalt was transported to the fluidized bed by a pipeline pump. The acidified Al2O3 and Ni-loaded phosphoaluminum molecular sieve were used as catalysts. The reaction temperature was set to 460℃, the hydrogen partial pressure was 6MPa, and the space velocity was 10h -1The hydrogenation treatment was carried out under the following conditions, and the hydrogenated product was transported to a vacuum distillation apparatus for treatment, with a negative pressure of 3 mmHg, 20 theoretical plates, a reflux ratio of 5:1, and a liquid phase distillation temperature of 330°C. 200 g of refined distillate oil was weighed and placed in a high-temperature and high-pressure reactor, 2 g of phosphoaluminic acid and 2.5 g of ferrophosphic acid were added, and the mixture was reacted at 400 ° C and 2 MPa for 6 h to obtain a two-phase coexistence asphalt containing intermediate phase beads. A mixed fraction of 130 ° C catalytic cracking gasoline fraction and 250 ° C coking diesel oil fraction in a mass ratio of 5:1 was used as an extractant. The agent-oil ratio during the extraction process was 5:1. Carbon microspheres were obtained by multiple elutions. The difference from Example 3 is that pre-oxidation was performed before carbonization treatment. The pre-oxidation temperature was set to 280 ° C, the oxygen flow rate was 300 ml / min, and the pre-oxidation time was set to 5 h. The pre-oxidation treatment was then carried out under a nitrogen atmosphere at 1000 ° C for 2 h, wherein the nitrogen flow rate was 200 ml / min, and carbon microspheres with an average particle size of 16.8 μm were obtained. The particle size distribution was uniform and the sphericity was good (refer to the relevant pictures of Example 3).

[0052] It can be seen from Examples 1 to 4 that the mesocarbon microspheres prepared in the present invention have uniform particle size distribution, good sphericity and high quality.

[0053] The purpose of the present invention is to realize high added value utilization of naphthenic heavy oil and obtain high-quality mesophase carbon microspheres. The present invention provides a method for preparing mesophase carbon microspheres. The method uses naphthenic heavy oil as a raw material, firstly adopts a low-temperature thermal polycondensation process to prepare a precursor asphalt, and then uses a suitable isomerization functional catalyst and a molecular sieve catalyst under suitable reaction conditions to perform ebullated bed hydrogenation treatment on the precursor asphalt to obtain a refined aromatic-rich fraction oil with a boiling range greater than 400°C. Using the refined aromatic-rich fraction oil as a raw material, a catalytic polycondensation reaction is carried out under the dual action of heteropolyacid aluminum salt and heteropolyacid iron salt catalyst to obtain a product asphalt containing mesophase beads, and then an organic solvent and an oil fraction are used for extraction, the isotropic asphalt component is removed, and after pre-oxidation and carbonization treatment, the mesophase carbon microspheres with uniform particle size distribution and good sphericity are obtained.

Claims

1. A method for preparing mesocarbon microspheres, characterized in that: The steps include: S1: Using naphthenic aromatic-rich heavy oil as raw material, a low-temperature thermal polycondensation process is used to prepare precursor asphalt; S2: The precursor asphalt is treated with ebullated bed hydrogenation using an isomerization catalyst and a molecular sieve catalyst, and then a vacuum distillation process is performed to obtain a refined aromatic-rich fraction oil; S3: using the refined aromatic-rich fraction oil as a raw material, carrying out a catalytic polycondensation reaction under the dual catalytic action of a heteropolyacid aluminum salt catalyst and a heteropolyacid iron salt catalyst to obtain an intermediate pitch containing mesophase beads, and extracting the intermediate pitch with an organic solvent or an oil fraction to obtain carbon microspheres; S4: subjecting the raw carbon microspheres to carbonization treatment or pre-oxidation and carbonization treatment to obtain intermediate carbon microspheres.

2. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The reaction temperature of the low-temperature thermal polycondensation process is 300° C. to 400° C., the reaction time is 10 min to 120 min, and the reaction pressure is 0.1 MPa to 3 MPa.

3. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The ebullient bed hydrogenation process temperature is 380°C to 460°C, the hydrogen partial pressure is 0.5MPa to 6MPa, and the space velocity is 0.1h -1 ~10h -1 .

4. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The isomerization functional catalyst is selected from one or more of AlCl3, SbCl, acidified Al2O3 or molybdenum oxide, the molecular sieve catalyst is selected from silicon aluminum molecular sieve or phosphorus aluminum molecular sieve, and the molecular sieve catalyst is loaded with one or more of Pt, Pd or Ni.

5. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The vacuum distillation process has a negative pressure of 1 to 5 mmHg, a theoretical number of towers of 5 to 20, a reflux ratio of 1:5 to 5:1, and a liquid phase distillation temperature of 330 to 350°C.

6. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The heteropolyacid aluminum salt catalyst is selected from one or more of phosphate aluminum acid, silicic acid aluminum acid or potassium phosphate aluminum salt, and the addition amount of the heteropolyacid aluminum salt catalyst is 0.5-5wt%.

7. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The heteropolyacid iron salt catalyst is selected from one or more of ferrophosphite, ferrophosphite divanadic acid or ferrophosphite trivanadic acid, and the addition amount of the heteropolyacid iron salt is 0.5-5wt%.

8. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The catalytic polycondensation reaction temperature is 350° C. to 450° C., the reaction pressure is 0.1 to 3 MPa, and the reaction time is 2 to 10 hours.

9. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The organic solvent is selected from one or more of tetrahydrofuran, N-dimethylformamide or dimethyl sulfoxide, and the solvent-oil ratio during the extraction process is 4:1 to 10:1; The oil fraction is selected from gasoline fraction with a boiling range of 130-200° C., diesel fraction with a boiling range of 200-350° C., or a mixed fraction of the two with a mass ratio of 5:1-1:

5. The agent-oil ratio during the extraction process is 1:1-10:

1.

10. The method for preparing mesocarbon microspheres according to claim 1, characterized in that: The pre-oxidation treatment temperature is 220°C to 280°C, the oxygen flow rate is 100 to 300 ml / min, and the pre-oxidation treatment time is 2h to 6h; the carbonization temperature is 800°C to 1600°C, the nitrogen flow rate is 100 to 300 ml / min, and the carbonization treatment time is 0.5h to 3h.

Citation Information

Patent Citations

  • Method of preparing mesocarbon microbeads by coal liquefaction residues and mesocarbon microbeads

    CN103613089A

  • Mesocarbon microbead, and method for preparing mesocarbon microbead from asphalt thermal cracking oil

    CN109179371A

  • Copolycondensation preparation of intermediate phase carbon microsphere

    CN1308113A

  • Preparation method of mesophase carbon microspheres from coal liquefaction residues

    CN102225755A

  • Device and method of light production of carbon microsphere by using residual oil / coal tar

    CN106753553A

Cited By

  • Process for preparing superconducting carbon black by refining and separating catalytic slurry oil

    CN122302936A